Educational Innovation - MutaqinEncep Jendi (International Conference on Elementary Education, 2021)
The progress and changes in human life are fast-paced, are new challenges or problems in the world of education. How should we prepare our students so that they can face modern life and how they can develop it so that they can compensate for these changes. Therefore, the teacher as a facilitator must be able to utilize electronic equipment facilities as a medium to be able to streamline the learning process, the teacher must also be able to choose methods, strategies, and learning models that suit their teaching needs. To answer all these challenges or problems, it is necessary to have an educational innovation. Discussions in the field of education must always be carried out to improve the quality of human resources in Indonesia. The purpose of this paper is to describe educational innovation, educational innovation processes, educational innovation strategies, characteristics of educational innovation, and barriers to educational innovation. The research method used is library research by recording all findings related to educational innovation. Educational innovation is a renewal in education that is carried out deliberately to improve educational goals, be it the renewal of ideas or ideas, renewal in educational practice, or renewal of methods or objects.